Ecomoral Imperative: Sources and Content - Kalenda, Česlovas (Problemos, 1996)
Eco-imperatiye has be coined by the scientists in response to the global eco-crisis and as the warning about an approaching threat. Intellectual sources of this regulative principle are old. They are connected with the idea of necessary moral control of the activities in science and technology. The imperative reflects aspirations of mankind to protect the favourable conditions for the existence of every species of animal nature. This aim demands from man to reckon with eco-laws implying moral choice to preserve life on the Earth.